Civics and citizenship multimedia presentation [videorecording (DVD)] : a promise of freedom : an introduction to U.S. history and civics for immigrants : becoming a U.S. citizen : an overview of the naturalization process (U.S. Dept. of Homeland Security, U.S. Citizenship and Immigration Services : For sale by the Supt. of Docs., U.S. G.P.O., 2010)
A Promise of Freedom is an inspiring short film for immigrant audiences based on the National Constitution Center's award-winning presentation Freedom Rising. This 12 minute film focuses on the history and founding of our nation and the important rights and responsibilities of U.S. citizenship. The role of immigration in U.S. history is highlighted throughout the film. Accompanying the DVD is a discussion booklet that aims to encourage discussion and review the basic concepts of American democracy outlined in the film. A Promise of Freedom is an excellent way to begin a session on immigration or citizenship.